The Role of Blockchain Technology in Enhancing Transparency in Public Administration - Denok Sunarsi (Universitas Negeri Makassar, 2023)
Blockchain technology has emerged as a transformative tool with the potential to revolutionize various industries, including public administration. This article aims to explore the role of blockchain technology in improving transparency in public administration. It provides an overview of the technology, discusses its key features, and examines its application in enhancing transparency within public sector operations. Furthermore, this article highlights the potential implications of blockchain adoption and concludes with insights into the future prospects of this technology in public administration.